PERAN PENDAMPINGAN PASTORAL TERHADAP PASIEN DI RS HKBP BALIGE - Butarbutar, Kesya; Lumban Gaol, Elisabeth; Sinaga, Geby; Silitonga, Derselli P. (POIMEN Jurnal Pastoral Konseling, 2025)
Pastoral care plays an important role in providing spiritual and emotional support for patients in hospitals. This study aims to analyze the role of pastoral care for patients at HKBP Balige Hospital and its impact on the psychological and spiritual conditions of patients. The research method used in this paper is a qualitative approach with interviews and direct observation of patients and pastoral care. The results of the study indicate that pastoral care helps improve inner peace, strengthen faith, and provide motivation for patients in dealing with their illnesses. In addition, pastoral care also plays a role in building harmonious relationships between patients, families, and medical personnel. Thus, pastoral care at HKBP Balige Hospital has a significant contribution in supporting patient recovery, both mentally and spiritually.